INNOVATIVE GASIFICATION TECHNOLOGY FOR THE CIRCULAR ECONOMY - Perne, Teos; Šetinc Ph.D, Marko; Seljak , Tine (Journal of Energy Technology, 2024)
This article presents a novel gasification technology process in the context of achieving carbon neutrality by establishing a sustainable circulation of carbonaceous materials with a focus on the production of virgin materials from various kinds of waste. The technology can alleviate the key limitations of existing gasification systems, which are the production and management of residue tars. The innovative technology process re-utilizes tars within the reaction itself, enabling an endless cycle of carbon. It also ensures high flexibility for efficiently handling heterogenic waste materials.